Moderation techniques for user-generated content in place-based communication - Coutinho, Pedro (2017)
Public displays can play a particularly important role in place-based communication because of their unique capability to expose their message in a contextually relevant way to anyone nearby, breaking personal filter bubbles and enabling situated shared experiences. However, before they can become an effective communication medium, they need to move towards more open models, where users are able to contribute with their own content. The key challenge is how to share control with users while being able to guarantee that published content matches the social expectations of a place. The key contribution of this work is a wide perspective of the key moderation approaches described in the literature for pre-moderation and post-moderation. We have taken a comprehensive approach that uncovers the broad range of techniques that can be applied to support moderation of user-generated content, highlighting their specificities and how they can complement each other to provide a comprehensive approach to moderation in these scenarios. This should help display owners to reason about the combination of techniques that is able to reduce risk to a level that is deemed acceptable, while minimising the moderation effort and the impact on the willingness of users to publish their content.